Southern rectangular section of the Mandapa of the Adinatha Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the southern rectangular section of the mandapa (pillared hall) of the Adinatha Temple. It is separated from the central square via a tripartite archway. The arches have floral motifs, whereas the back wall of the southern wing has paintings of empty niches in low relief.